1996
DOI: 10.1073/pnas.93.6.2370
|View full text |Cite
|
Sign up to set email alerts
|

Internal ribosomal entry site substitution eliminates neurovirulence in intergeneric poliovirus recombinants.

Abstract: Neuropathogenicity of poliovirus can be attenuated by mutations in the internal ribosomal entry site (IRES) within the 5' nontranslated region of its genome. The Sabin vaccine strains used in prevention of poliomyelitis carry such mutations in their IRES elements. In addition, mutations within the structural and nonstructural proteins of Sabin strains may equally contribute to the attenuation phenotype. Despite their effectiveness as vaccines, the Sabin strains retain a neuropathogenic potential in animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
315
1
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(334 citation statements)
references
References 28 publications
12
315
1
6
Order By: Relevance
“…The fact that PV-infected CD155 tg mice develop poliomyelitis bearing the hallmarks of the primate disease (12)(13)(14) underscores the cardinal role of receptor preference in EV disease specificity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that PV-infected CD155 tg mice develop poliomyelitis bearing the hallmarks of the primate disease (12)(13)(14) underscores the cardinal role of receptor preference in EV disease specificity.…”
mentioning
confidence: 99%
“…Plasmid pCAV21 (strain Kuykendall) was cut with MluI and transcribed in vitro with T7 RNA polymerase (Stratagene) to derive virus, as described (14). Anesthetized mice (10-28 wk old) were injected with CAV21 [2.8 ϫ 10 8 plaque-forming units (pfu) in 30-100 l of PBS] into the gastrocnemius muscle with a 27-gauge needle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A very similar footprint pattern was obtained when the experiment was carried out with nuclear extracts of mouse L cells (data not shown), a result suggesting that factors controlling hPVR promoter activity and transcriptional start site selection are similar in human and mouse cells. This was not unexpected, since mice transgenic for the hPVR gene are not only sensitive to poliovirus infection, but when inoculated intravenously or intracerebrally, they produce a disease syndrome nearly identical to human poliomyelitis (24,25,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that the effect of reduced viral protein synthesis activity in the range examined on the attenuation of PV was limited, hence other steps in the infection process may play major roles in the attenuation. The mutants examined in this study make a contrasting example to the RIPO mutant, which is a PV mutant with rhinovirus IRES that replicated well in HeLa cells but was not neurovirulent in PV receptor-expressing transgenic mice (Gromeier et al, 1996).…”
Section: Discussionmentioning
confidence: 99%